Pengaruh Kualitas Layanan dan Teknologi Informasi terhadap Kepuasan Nasabah Bank SulutGo Cabang Calaca - Rompas, Sefea Viarosa (JURNAL ADMINISTRASI BISNIS, 2026)
This study aims to analyze the influence of service quality and information technology on customer satisfaction at Bank SulutGo, Calaca Branch. The research employs a quantitative approach using an associative method to examine relationships between variables. The sample consisted of 96 active customers of Bank SulutGo Calaca Branch selected as respondents. Data were collected through questionnaires and interviews and analyzed using validity tests, reliability tests, classical assumption tests, correlation analysis, multiple linear regression analysis, t tests, F tests, and the coefficient of determination. The findings indicate that service quality has a positive and significant effect on customer satisfaction, as shown by a calculated t value greater than the t table value (4.444 > 1.985). Information technology also has a positive and significant effect on customer satisfaction, evidenced by a calculated t value exceeding the t table value (6.698 > 1.985). Simultaneously, service quality and information technology significantly influence customer satisfaction. The coefficient of determination (R²) of 0.673 indicates that 67.3 percent of the variation in customer satisfaction can be explained by service quality and information technology, while the remaining 32.7 percent is influenced by other variables not included in this study. These results suggest improving customer satisfaction through better technology.